(b+10)(3b)b=

Simple and best practice solution for (b+10)(3b)b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (b+10)(3b)b= equation:


Simplifying
(b + 10)(3b) * b = 0

Reorder the terms:
(10 + b)(3b) * b = 0

Remove parenthesis around (3b)
(10 + b) * 3b * b = 0

Reorder the terms for easier multiplication:
3b * b(10 + b) = 0

Multiply b * b
3b2(10 + b) = 0
(10 * 3b2 + b * 3b2) = 0
(30b2 + 3b3) = 0

Solving
30b2 + 3b3 = 0

Solving for variable 'b'.

Factor out the Greatest Common Factor (GCF), '3b2'.
3b2(10 + b) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'b2' equal to zero and attempt to solve: Simplifying b2 = 0 Solving b2 = 0 Move all terms containing b to the left, all other terms to the right. Simplifying b2 = 0 Take the square root of each side: b = {0}

Subproblem 2

Set the factor '(10 + b)' equal to zero and attempt to solve: Simplifying 10 + b = 0 Solving 10 + b = 0 Move all terms containing b to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + b = 0 + -10 Combine like terms: 10 + -10 = 0 0 + b = 0 + -10 b = 0 + -10 Combine like terms: 0 + -10 = -10 b = -10 Simplifying b = -10

Solution

b = {0, -10}

See similar equations:

| 4(x+6)-2(x-4)=40 | | V+1-2v=5 | | -8*-5/2 | | -12*3= | | 84=x+37 | | d^2=16 | | -4k+2k=-2 | | 4(x+5)=2(3x)+14 | | Cos22°(3/5) | | -1/8(3/5) | | y=0.0006x+1E-17 | | -5d-3.5d=26.5 | | 20-(x+9)=6x-3 | | 5s+27=172 | | x^2-14x-53=0 | | -3/5*-1/9 | | 2-n=-1 | | t+12=12 | | 25.56+x=25.72 | | 14-3f=2 | | x-10=3x-12 | | -2-n=0 | | 90=-2(3-6k) | | 3r+19=4-2r | | logx=0.32 | | 2(x+6)=3(x+7) | | x+1=12x-1 | | 3/5*(-1/6) | | 3r/10=6 | | -2.73+x=-.3 | | q/-5=18 | | 2log(3x+5)=4 |

Equations solver categories